TEACHER’S ROLE IN MANAGING THE FIFTH-GRADE STUDENTS’ MENTAL-EMOTIONAL HEALTH AT KEBAREPAN 1 ELEMENTARY SCHOOL - Salsabilla Ramadhanti; Nurdinah Hanifah; Cucun Sunaengsih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The increasing number of mental health issues in Indonesia and the limited research studied on mental-emotional health issues, in general, are the background of this paper, especially among elementary students. It is to investigate the role and obstacles of elementary school teachers regarding the students’ mental health characteristics and social-emotional conditions. The research implication is that teachers play a crucial role in managing students' mental-emotional health to build positive values and attitudes in order to have good personalities at school. Therefore, teachers need to have the skills to control their own emotions well in order to support them to act in healthy physical and mental activities. The research used a qualitative approach using phenomenological research methods. The research participants included teachers and 44 fifth-grade students of SDN 1 Kebarepan. Data collection used interviews, observations, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion. The results indicate that the teachers have been carrying out their roles in managing students' emotional conditions, even though it doesn’t implement totally yet as the environment lived by students can also provide an impact on their mental-emotional health development.